Mechanisms Underlying Pioglitazone-Mediated Relaxation in Isolated Blood Vessel - Hidemi Nomura; Hideyuki Yamawaki; Masashi Mukohda; Muneyoshi Okada; Yukio Hara (Elsevier, 2008)
Pioglitazone is a widely used anti-type 2 diabetic drug. Beside its insulin-sensitizing effects, pioglitazone exerts preventive roles against ischemic heart disease. Since one possible explanation is anti-hypertensive action, we examined effects of pioglitazone on contractility of isolated blood vessel. Endothelium-intact [End (+)] or -removed [End (−)] rat aorta is isolated and isometric tension is recorded. In both End (+) and End (−) aorta, pretreatment with pioglitazone (3 -10 μM, 30 min) inhibited noradrenaline (NA) (1 nM -1 μM)-induced contraction. In NA (100 nM)-pre-contracted aorta, pioglitazone (1 -10 μM) directly induced a relaxation. The relaxant effect is higher in End (−) aorta than in End (+) aorta. In End (+) aorta, NG-nitro-L-arginine methyl ester (100 μM) significantly inhibited the relaxation. In End (−) aorta, neither indomethacin nor cimetidine affected the relaxation, but tetraethylammonium (10 mM) inhibited it. Furthermore, the relaxation was significantly inhibited by a voltage-dependent K+ (KV)-channel blocker, 4-aminopyridine (1 mM), or an inward rectifying K+ (KIR)-channel blocker, BaCl2 (1 mM). GW9662 (2 μM), a blocker of peroxisome proliferator-activated receptor (PPAR)-γ was ineffective against the relaxation. The present study demonstrated that pioglitazone causes PPAR-γ-independent relaxation. While endothelium-dependent relaxation is mediated via nitric oxide, the endothelium-independent one is responsible for smooth muscle K+ (KV, KIR)-channel opening. Keywords:: diabetes, endothelium, smooth muscle, nitric oxide, potassium channel